3D‐Printing of Functionally Graded Porous Materials Using On‐Demand Reconfigurable Microfluidics. (29th April 2019) - Costantini, Marco; Jaroszewicz, Jakub; Kozoń, Łukasz; Szlązak, Karol; Święszkowski, Wojciech; Garstecki, Piotr; Stubenrauch, Cosima; Barbetta, Andrea; Guzowski, Jan
Abstract: Tailoring the morphology of macroporous structures remains one of the biggest challenges in material synthesis. Herein, we present an innovative approach for the fabrication of custom macroporous materials in which pore size varies throughout the structure by up to an order of magnitude. We employed a valve‐based flow‐focusing junction (vFF) in which the size of the orifice can be adjusted in real‐time (within tens of milliseconds) to generate foams with on‐line controlled bubble size. We used the junction to fabricate layered and smoothly graded porous structures with pore size varying in the range of 80–800 μm. Additionally, we mounted the vFF on top of an extrusion printer and 3D‐printed constructs characterized by a predefined 3D geometry and a controlled, spatially varying internal porous architecture, such as a model of a bone. The presented technology opens new possibilities in macroporous material synthesis with potential applications ranging from tissue engineering to aerospace industry and construction. Abstract : Schaum nach Bedarf : Durch Benutzung abrufbarer und rekonfigurierbarer Mikrofluidik können Schäume mit kontrollierbarer Blasengröße einfach produziert werden. Die Schäume dienen als Template für die Synthese neuer Materialien mit räumlich variierender Porenstruktur, was eine Vielzahl von Anwendungen ermöglicht.